Can Exclusive Breastfeeding Prevent Stunting in Lower Middle-income Countries (LMIC)?: A Systematic Review - Rhisma Nasita Sianti; Martha Irene Kartasurya; Apoina Kartini (PT FORMOSA CENDEKIA GLOBAL, 2024)
Stunting, a nutritional concern, exerts adverse effects by influencing the physical and functional attributes of a child's body, contributing to elevated rates of child morbidity. Globally, the prevalence of stunting remains considerably high, registering at 22.2% in 2017, with approximately 55% of affected children in Asia and 39% in Africa. To Evaluate the connection between exclusive breastfeeding and stunting rates in lower middle-income countries. The research design was a systematic review. Article searches were conducted using Google Schoolar, Pubmed, Science Direct, and Scopus databases. The keywords used were